Konsep Pengendalian Intern Untuk Keamanan Sistem Informasi - Sayuthi Sayuthi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
The purpose of this article is to determine the concepts of good control to be applied in a corporate organizational environment. Based on several concepts offered, the control based on Sarbanes-Oxley and Internal Control (COSO Framwork) is still highly recommended by experts. This is because the control concept of this model has adopted all existing aspects of protection, both physical and non-physical. However, security protection for information systems should ideally be focused on access control and IT control. There are three groups of individuals who differ in their normal ability to access hardware, namely; 1) Personal computer systems, which often pose a potential bottleneck because they often have special access to important data and programs. 2) Users, they have narrower access, but they still have the opportunity to commit embezzlement. 3) The intruders, they do not have access at all, but they are often people who have the ability to interfere with company information systems.